Elaboração de biofilmes a partir da pectina extraída do mesocarpo da laranja pera - Ramos, Alice Cristini dos Santos (2021)
Due to the growing environmental concern with the accumulation of non-renewable materials and the management of agro-industrial residues, there is great interest in the development of biofilms, which in addition to minimizing the use of traditional synthetic films of petrochemical origin, offer an option for compatible use of waste generated in agribusiness. Biofilms are pre-formed thin membranous structures, made up of natural polymers (lipids, polysaccharides, and proteins), capable of forming a continuous and cohesive matrix, associated or not with a plasticizer and solvent. Pectin stands out for being one of the most used natural polysaccharides in the development of biodegradable films, due to its easy extraction, abundance in nature and absence of toxicity. This polymer is found in fruit peels, for this reason, the present work aimed to develop and characterize biofilms from pectin extracted from the mesocarp of orange cv. Pera, the most cultivated citrus variety in Brazil. In this study, pectin films with glycerol as plasticizer were prepared using the casting methodology. The process was carried out acid extraction of pectin from the orange mesocarp, with an average yield of 23.54%. The developed films presented a homogeneous appearance, without cracks and insoluble particles. Other characteristics found in this study were the biodegradability of the films, the low tensile strength (0.87 kPa) and elongation (22.84%) and the high solubility and moisture (62.05%). It was also verified that the developed films can be used to preserve the ready-made pastry dough, since this product kept its softness without the visible presence of fungi and bacteria, by being protected by the manufactured biofilm, although it acquired a more yellowish color. It is observed that the biofilms produced from pectin extracted from the mesocarp of the Pera orange were developed using a simple methodology, thus demonstrating that there is a possibility of using residues from fruit processing industries for production without the intensive control of the biofilms formulations.